Joint submission of CGIAR and the Eastern Africa Farmers Federation in response to Decision 2/CMA.5, Paragraph 41 regarding the United Arab Emirates Belem Work Programme on indicators - CGIAR; Alliance of Bioversity International and CIAT; International Livestock Research Institute; International Water Management Institute; Eastern Africa Farmers Federation (CGIAR System Organization, 2024)
The GGA framework outlines eleven broad thematic and dimensional targets. The targets need to be unpacked to be operational. For example, Target 9 (b) on food and agriculture highlights elements critical to resilient food production, distribution, and consumption. The focus on resilience captures the outcomes that should collectively be achieved. However, it omits elements that are more practical to measure, including the adaptation practices and strategies that must be implemented across scales to achieve these outcomes. It will be essential to use a framework that can help identify the actions, outcomes, their connections, and corresponding indicators that are relevant and can be tailored for various vulnerability contexts. Impact pathways/ theories of change provide a scientifically validated and well-known approach to do so. For example, CGIAR’s analysis of investment priorities articulated in national investment plans across Africa distilled key impact pathways for adaptation and resilience. These impact pathways guided the selection of indicators corresponding to specific actions and expected outcomes. They also helped uncover diverse adaptation priorities of countries and their ambitions and the indicators for assessing progress at the farm, subnational, and national scales. The indicators also cover social, economic, and ecological components of agricultural systems, underscoring the linkages between the thematic targets of the GGA framework. The consideration of the contextually relevant hazards, adaptations, actions, and expected outcomes also helped identify indicators corresponding to the dimensional targets.